Begging Activities in Pontianak City: Analysis of Driving Factors and Their Impact on the Environment and Children - Jenisa Zeldzean; Siti Aisyah; Miko Rahmadi; Fuzy Firda Zhan (Cita konsultindo, 2024)
Looking at the facts on the ground, most of the beggars are not all poor or homeless, some of them are just pretending to attract the sympathy of many people by bringing children. This practice cannot be justified because it involves the exploitation of children and is a violation of children's rights. This research analyzes the driving factors and impacts on children and the environment in begging activities in Pontianak City. The method used in this research is a literature study where the researcher collects various literature to obtain research data. The research results show that several driving factors cause beggars to bring children when begging, such as economic factors, social factors, and educational factors which are the main factors. The research results also reveal the impact of begging with children on the surrounding environment which can affect other individuals or groups. The recommendation from this research is that the state needs to be more assertive in taking preventive measures to reduce the practice of begging with children and its negative impact on the surrounding environment and the children involved.